The Urgency of a Compassionate Attitude as a Key Pillar of Religious Moderation in Indonesia - Muh. Shobban Madda Ilahi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This research examines the importance of tolerance as the main foundation for religious moderation in Indonesia. The issue raised is related to the increase in conflict and intolerance that threatens interreligious harmony. This study confirms that tasamuh, which is an attitude of tolerance and appreciation for differences, is crucial for maintaining cultural and religious diversity at the national level. The approach used includes literature reviews and literature studies. This finding indicates that the implementation of tolerance is capable of strengthening religious moderation, reducing radicalism, and increasing social harmony. Additionally, this research provides strategic recommendations for strengthening education and public policy to instill the value of tolerance in community life.